Carbon dioxide emissions quotas allocation in the Pearl River Delta region: Evidence from the maximum deviation method. (10th March 2018) - Li, Lixu; Li, Yina; Ye, Fei; Zhang, Li
Abstract: To achieve the Chinese government's CO2 emissions reduction target and build a carbon trading market in the Pearl River Delta (PRD) region, an initial allocation of CO2 emissions quotas among cities in this region is fundamental. Different from the previous CO2 emissions quotas allocation methods, this paper uses the maximum deviation method (MDM) to allocate CO2 emissions quotas in the PRD region by taking the imbalanced development of different cities into consideration. Three principles including equality (represented by a population indicator), efficiency (represented by a GDP indicator) and feasibility (represented by a historical CO2 emissions indicator) are considered in the method. The results reveal that the allocations derived by the MDM are more balanced than those derived using either single indicator approach or the information entropy method, and more closer to the development targets of Guangdong province. The more balanced allocations will be conducive to stimulating the development of under-developed cities and narrowing the gap between developed and under-developed cities, thus help to achieve the sustainable development in the PRD region. This paper helps to enrich the emissions quotas allocation methods and provides a new equitable method for policy makers to allocate emissions quotas under imbalanced development circumstances. Highlights: The maximum deviation method is adopted in the CO2 quotas allocation issue. Equality, efficiency and feasibility principles are considered in the method. The allocation results are compared among different methods. The advantage and feasibility of maximum deviation method is manifested. The implications for policy makers are highlighted.